2015
DOI: 10.1515/zna-2014-0252
|View full text |Cite
|
Sign up to set email alerts
|

Soret and Dufour Effects in the Flow of Williamson Fluid over an Unsteady Stretching Surface with Thermal Radiation

Abstract: This paper looks at the simultaneous effects of heat and mass transfer in the flow of Williamson fluid over an unsteady stretching surface. The effects of thermal radiation and viscous dissipation are considered in an energy equation. Besides, the energy and concentration equations are coupled with the combined effects of Soret and Dufour. The convective conditions for both temperature and mass concentration are employed. The transformation procedure reduces the time-dependent boundary layer equations of momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Nadeem and Hussain [15] found series solution of Williamson nanofluid flow over a stretching sheet. Hayat et al [16] also studied Williamson fluid flow analytically using homotopy analysis method in attendance of viscous dissipation, Newtonian Joule heating. Malik and Salahuddin [17] discussed numerical simulation of MHD Williamson fluid flow near stagnation point using RK–Fehlberg method over a stretched cylinder.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Nadeem and Hussain [15] found series solution of Williamson nanofluid flow over a stretching sheet. Hayat et al [16] also studied Williamson fluid flow analytically using homotopy analysis method in attendance of viscous dissipation, Newtonian Joule heating. Malik and Salahuddin [17] discussed numerical simulation of MHD Williamson fluid flow near stagnation point using RK–Fehlberg method over a stretched cylinder.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Salahuddin et al [49] reported flow of Williamson fluid over stretching surface using the theory of Cattaneo-Christov for heat and mass transfer developments. Whereas Soret and Dufour effects on Williamson fluid flow was reported by Hayat et al [50] using convective conditions. The results indicate that thermal as well as solute Biot numbers are increasing factors for temperature field.…”
Section: Introductionmentioning
confidence: 85%
“…Since fluid is electrically conducting, so magnetic field is imposed in y direction. The governing equations for this flow problem are expressed as follows [11]:…”
Section: Flow Analysismentioning
confidence: 99%
“…Kumar et al [10] provided the numerical expressions of Williamson liquid through suspended particles under non-linear solar radiation aspects. Hayat et al [11] used convective boundary conditions to investigate magnetohydrodynamic flow of Williamson fluid induced by continuously moving surface.…”
Section: Introductionmentioning
confidence: 99%